iMEC: Online Marker Efficiency Calculator - Amiryousefi, Ali; Hyvönen, Jaakko; Poczai, Péter (Applications in plant sciences, 2018)
Premise of the Study To accurately design plant genetic studies, the information content of utilized markers and primers must be calculated. Plant genotyping studies should take into account the efficiency of each marker system by calculating different parameters to find the optimal combination of primers. This can be problematic because there are currently no easily accessible applications that can be used to calculate multiple indices together. Methods and Results The program Online Marker Efficiency Calculator (iMEC) was developed using R for the simple computation of seven polymorphism indices (heterozygosity index, polymorphism information content, discriminating power, effective multiplex ratio, marker index, arithmetic mean heterozygosity, and resolving power). These indices are based on dominant and codominant DNA fingerprinting markers, thus allowing comparison and selection of optimal genetic markers for a given data set. Conclusions iMEC simplifies the calculation of diverse indices for the marker of choice to better enable researchers to measure polymorphism information for individual markers. The program is available at https://irscope.shinyapps.io/iMEC/.